Rebranding Program Rumpi Kuliner SHE Radio 99,6 FM Surabaya - Yuliana Sukma Dewi; Nurtyasih Wibawanti Ratna Amina (DIGICOM : Jurnal Komunikasi dan Media, 2022)
This study aims to investigate how the programming approach of a Surabaya radio station, She Radio 99.6 FM, in rebranding the Rumpi Kuliner program to catch listeners' interest. One of She Radio 99.6 FM's rebranding initiatives is the Culinary Rumpi program, which features broadcasts in the style of small talk from resource people and presenters who previously hosted the Rumpi Kuliner Dapur Manda program This name change was made to adjust the segmentation of middle-class housewives and to remove the figure element from the program name, this was also done due to a change in the program announcer. This study will conduct a qualitative descriptive analysis using the concepts of compatibility, habit formation, control of audience flow, and resource conservation from the data that has been gathered through interviews and direct observation (resource conservation). Sydney W. Head proposed the idea of broad reach, program power, and the urge to investigate She Radio 99.6 FM's strategic program in the Rumpi Kuliner rebranding initiative. Researchers have discovered that She Radio 99.6 FM is capable of rebranding the Rumpi Culinary program in accordance with the five factors by taking into account the preferences and interests of the audience.